1998
DOI: 10.1002/pro.5560070316
|View full text |Cite
|
Sign up to set email alerts
|

Tetramer‐dimer equilibrium of oxyhemoglobin mutants determined from auto‐oxidation rates

Abstract: One of the main difficulties with blood substitutes based on hemoglobin (Hb) solutions is the auto-oxidation of the hemes, a problem aggravated by the dimerization of Hb tetramers. We have employed a method to study the oxyHb tetramer-dimer equilibrium based on the rate of auto-oxidation as a function of protein concentration. The 16-fold difference in dimer and tetramer auto-oxidation rates (in 20 mM phosphate buffer at pH 7.0, 37 "C) was exploited to determine the fraction dimer. The results show a transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 64 publications
(84 reference statements)
2
39
1
1
Order By: Relevance
“…7D). Interestingly IHP, an allosteric effector that also pushes the tetramer-dimer equilibrium toward tetramer at low concentrations, but toward dimers when used at high concentrations as was the case in our studies (42)(43)(44)(45)(46)(47)49), showed an increased observed rate constant similar to those seen by dimers at both 50 and 25 M ProliNO (see Fig. 5).…”
Section: Effects Of T-state Stabilization and Ph Onsupporting
confidence: 54%
See 1 more Smart Citation
“…7D). Interestingly IHP, an allosteric effector that also pushes the tetramer-dimer equilibrium toward tetramer at low concentrations, but toward dimers when used at high concentrations as was the case in our studies (42)(43)(44)(45)(46)(47)49), showed an increased observed rate constant similar to those seen by dimers at both 50 and 25 M ProliNO (see Fig. 5).…”
Section: Effects Of T-state Stabilization and Ph Onsupporting
confidence: 54%
“…Experiments run at 15°C confirmed this trend, with IHP being more effective at increasing the rate constants at lower temperature. The reasons for these temperature effects of IHP on rates are not clear, but we speculate that IHP has two effects: it speeds up the reaction through the stabilization of the T-state but also may promote the formation of HbA dimers when used at high concentrations (42)(43)(44)(45)(46)(47). These hemoglobin dimers can also cause the reaction to speed up as discussed below.…”
Section: Effects Of T-state Stabilization and Ph Onmentioning
confidence: 99%
“…Higher order multimers are not necessarily observed using other methods such as SDS-PAGE [47]. The tetramers and dimers cannot be separated by chromatography because they interchange on a time scale of seconds [48]. However, careful fitting of chromatographic peak shapes allows detection of the dimers and determination of the dissociation equilibrium constant.…”
Section: Mass Spectra Of Hemoglobinmentioning
confidence: 99%
“…Occasionally, this was complemented by CD and fluorescence spectroscopic measurements [27,28]. Other studies were based on measurements of haptoglobin binding [29], autooxidation kinetics [30], radioactive labeling [31], as well as stopped-flow pH measurements [32]. The in vitro assembly of Hb has most commonly been triggered by mixing initially separated ␣ h and ␤ h subunits under native solvent conditions.…”
mentioning
confidence: 99%